IMPLEMENTASI UNDANG-UNDANG NOMOR 25 TAHUN 2009 TENTANG PELAYANAN PUBLIK DIKANTOR CAMAT KECAMATANSEMATANG BORANG KOTA PALEMBANG(STUDI KASUS PASAL 34) - Iasha, Citra; Aripah, Sabrina Zakirah (STIA SATYA NEGARA PALEMBANG, 2022)
Public service is an activity or series in the context of fulfilling service needs in accordance with statutory regulations for every citizen or resident of goods, services or administrative services provided by public administrators. Implementers of public services, hereinafter referred to as implementers, are officials, employees, officers and everyone working in organizations providing public services.This study aims to analyze the implementation of Law No. 25 of 2009 concerning Public Services at the Sematang Borang Sub-district Head Office, Palembang City (Case Study Article 34). This research was conducted using qualitative methods. Data collection techniques used through observation, interviews, documentation and literature study. Data analysis techniques are carried out by collecting data, reducing data, presenting data and drawing conclusions.Based on the results of the research and discussion, it can be concluded that the implementation of Law Number 25 of 2009 concerning Public Services at the Subdistrict Office of Sematang Borang, Palembang City (Case Study Article 34) has been carried out well, this can be seen from the employees who have provided their best service even though there are still services that have not been carried out properly, but the employees at the sematang borang Formal sub-district office will further improve the services at the sub-district office, so that the community is satisfied with the services provided by the employees. Keywords: Implementation, Public Service